Health‐related quality of life by human immunodeficiency virus status in a cross‐sectional survey of gay and bisexual prostate cancer survivors. Issue 12 (11th November 2019) - Polter, Elizabeth J.; Wheldon, Christopher W.; Rosser, B.R. Simon; Kohli, Nidhi; Capistrant, Benjamin D.; Kapoor, Aditya; Konety, Badrinath; Mitteldorf, Darryl; Ross, Michael; Talley, Kristine M.C.; Terveen, Loren; West, William; et al.
Abstract: Objective: Prostate cancer is the most common invasive cancer in gay and bisexual men (GBM). Despite the unique sexual and urinary concerns of this group, studies of prostate cancer rehabilitation have primarily focused on heterosexual men. GBM also have high prevalence of human immunodeficiency virus (HIV), which may be associated with lower health‐related quality of life (HRQOL). We examined the association between HIV status and HRQOL in a cohort of GBM with prostate cancer. Methods: Data from the Restore study, a cross‐sectional online survey of GBM treated for prostate cancer, were used to examine this association. The Expanded Prostate Cancer Index Composite (EPIC) assessed function, bother, and summary measures in four domains: urinary, sexual, bowel, and hormone. Overall physical and mental HRQOL was assessed using the Short‐Form Health Survey (SF‐12). Multivariate analysis of variance and linear regression were used to evaluate the association between HIV status and HRQOL scores after adjustment for demographic and sexual characteristics. Results: Of 192 participants, 24 (12.4%) reported an HIV diagnosis. After adjustment for covariates, HIV‐positive status was associated with lower scores on the EPIC urinary (mean difference [MD]: −13.0, 95% CI, −21.4 to −4.6), sexual (MD: −12.5, 95% CI, −21.9 to −3.2), and bowel (MD: −5.9, 95% CI, −11.7 to −0.2) domains. No significant associations were observed between HIV status and other outcomes. Conclusions: HIV status may be associated with poorer urinary, sexual, and bowel HRQOL in GBM prostate cancer survivors.